2015
DOI: 10.3892/ijmm.2015.2128
|View full text |Cite
|
Sign up to set email alerts
|

The inhibitory effects of Geranium thunbergii on interferon-γ- and LPS-induced inflammatory responses are mediated by Nrf2 activation

Abstract: Geranium thunbergii Sieb. et Zucc. (GT; which belongs to the Geraniaceae family) has been used as a traditional medicine in East Asia for the treatment of inflammatory diseases, including arthritis and diarrhea. However, the underlying mechanisms of the anti-inflammatory effects of GT remain poorly understood. In the present study, we examined the mechanisms responsible for the anti-inflammatory activity of GT in macrophages. The results revealed that GT significantly inhibited the lipopolysaccharide (LPS)- an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 42 publications
0
16
0
Order By: Relevance
“…The polyphenolic profile of the DICHO fraction of Geranium koreanum , which has beneficial bioactivity, was detected by LC-MS/MS. Geraniin is the main phenolic compound of Geranium species, and it is reported to have bioactive effects such as anti-inflammatory effects via regulation of NF-κB and Nrf2 pathways in Raw 264.7 cells, cytoprotective effect via regulation of BACH-1 and HO-1 in HepG2 cells, and anticancer effects via inhibition of NF-κB activation [ 10 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ]. Depending on the detector counts, the phenolic compounds of DGK are displayed in Table 1 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The polyphenolic profile of the DICHO fraction of Geranium koreanum , which has beneficial bioactivity, was detected by LC-MS/MS. Geraniin is the main phenolic compound of Geranium species, and it is reported to have bioactive effects such as anti-inflammatory effects via regulation of NF-κB and Nrf2 pathways in Raw 264.7 cells, cytoprotective effect via regulation of BACH-1 and HO-1 in HepG2 cells, and anticancer effects via inhibition of NF-κB activation [ 10 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ]. Depending on the detector counts, the phenolic compounds of DGK are displayed in Table 1 .…”
Section: Discussionmentioning
confidence: 99%
“…Geraniin was present in the DICHO fraction at RT 7.68 min ( Figure 7 ). It has been identified in Geranium wilfordii Maxim., Geranium sibiricum L., Geranium robertianum L., Geranium thunbergii [ 38 , 39 , 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Plant extracts of Geranium bellum and aqueous leaf extracts of Phyllanthusmuellerianus (Kuntze) have been shown to have anti-inflammatory activities with geraniin as the most potent compound [ 47 ]. Similarly, extracts of Geranium thunbergii significantly inhibit the LPS- and IFN-γ-induced expression of pro-inflammatory genes, such as iNOS, TNF-α and IL-1β [ 48 ] by a mechanism mediated by increased nuclear factor erythroid 2-related factor 2 (Nrf2) activity. Other studies using pure geraniin have validated these observations by showing that it is indeed geraniin that is responsible for the inhibition of LPS-induced inflammation by regulating NF-κB via the Nrf2 pathway in macrophages.…”
Section: Natural Pharmacological Modulatorsmentioning
confidence: 99%
“…Choi et al examined the anti-inflammatory activity of a 50% aqueous EtOH extract of G. thunbergii in bone marrow-derived macrophages (BMDM) activated by interferon-γ (INF-γ) and bacterial lipopolysaccharides (LPS) and found that the extract exerted a significant inhibitory effect on induced inflammation at non-toxic doses [159]. The anti-inflammatory effect seemed to be associated with the activation of the nuclear erythroid 2-related factor (Nrf2), a key transcription factor in anti-inflammatory systems.…”
Section: Anti-inflammatory Activitymentioning
confidence: 99%